Isolasi dan Identifikasi Bakteri Asam Laktat pada Pekasam Ikan Haruan: Efek Fermentasi dan Penggorengan - Safitri, Diah; Fitriah, Fitriah; Nashihah, Siti; Andika, Andika; Fajeriyati, Nurul (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to obtain lactic acid bacteria (LAB) isolates in fermented snakehead fish (Channa striata) pekasam and compare pekasam before and after frying with variations in fermentation time for 1 and 2 weeks. The type of research conducted in this study is experimental, whose testing starts from making pekasam using 30% salt and 50% rice from the total weight of the fish, isolation of LAB, gram staining test, scanning electron microscopy (SEM), and total plate number (ALT) testing. Data were analyzed using SPSS 27 to see significant differences between fermentation and frying times. The results showed that (1) there was LAB growth in all pekasam isolates before and after frying; (2) the results of gram staining showed that all isolates were gram-positive bacteria; (3) the results of SEM observation with a magnification of 12. 000, the morphology of bacillus-shaped bacteria with cell sizes ranging from 1.462 -1.682 µm was obtained; (4) ALT test results of LAB isolates in pekasam before frying in the first week showed results with a value of 1.90 x 106 CFU/mL and the second week 2.04 x 106 CFU/mL while LAB isolates of pekasam after frying in the first week were 0.63 x 106 CFU/mL and the second week 0.75 x 106 CFU/mL; (5) the results of data analysis obtained significant differences between the effects of fermentation and frying on ALT testing, It can be concluded that the longer the fermentation time can increase the total LAB in fermented snakehead fish (pekasam).